Association between varicose veins and occurrence of dementia: A nationwide population-based cohort study - Ho Geol Woo; Ju-young Park; Moo-Seok Park; Tae-Jin Song (PLoS ONE, 2025)
While varicose vein (VV) and dementia are frequent health problems, research investigating association between these conditions has been limited. We aimed to investigate the relationship between the presence of VV and the development of dementia, as well as to evaluate whether treatment for VV correlates with the occurrence of dementia in a longitudinal study involving the general population. Our study included 430,875 participants based on health screening results conducted from 2005 to 2010 in the South Korean health screening cohort database. Presence of VV was defined with at least two or more claims based on International Classification of Diseases, Tenth Revision (ICD-10) of I830-832, I839, or I868. Propensity score matching at a ratio of 1:5 was employed to categorize the participants into two groups based on the presence and treatment of VV, respectively. Primary outcome was the incidence of all-cause dementia with two or more claims based on ICD-10 code (F00-03, G30, and G31), and secondary outcomes considered occurrence of Alzheimer’s disease (AD; F00 or G30) and vascular dementia (VD; F01). Among included participants, presence of VV were noted in 5,096 (1.3%) participants. During a median follow-up of 13.33 (interquartile range 10.4–16.26) years, 55,329 (13.9%) cases of all-cause dementia have occurred. In multivariable analysis, VV group showed increased risk of all-cause dementia compared to non-VV group (hazard ratio [HR]: 1.235, 95% confidence interval [CI]: 1.147–1.329). Contrary to AD, treatment of VV group was significantly associated with decreased risk of VD (HR: 0.566, 95% CI: 0.382–0.841). Our study showed that presence of VV may be associated with an increased risk of future all-cause dementia, and treatment of VV was likely to reduce the incidence risk of VD.